CEP290 is essential for the initiation of ciliary transition zone assembly - Wu, Zhimao (PLoS Biol, 2020)
Cilia play critical roles during embryonic development and adult homeostasis. Dysfunction of cilia leads to various human genetic diseases, including many caused by defects in transition zones (TZs), the “gates” of cilia. The evolutionarily conserved TZ component centrosomal protein 290 (CEP290) is the most frequently mutated human ciliopathy gene, but its roles in ciliogenesis are not completely understood. Here, we report that CEP290 plays an essential role in the initiation of TZ assembly in Drosophila. Mechanistically, the N-terminus of CEP290 directly recruits DAZ interacting zinc finger protein 1 (DZIP1), which then recruits Chibby (CBY) and Rab8 to promote early ciliary membrane formation. Complete deletion of CEP290 blocks ciliogenesis at the initiation stage of TZ assembly, which can be mimicked by DZIP1 deletion mutants. Remarkably, expression of the N-terminus of CEP290 alone restores the TZ localization of DZIP1 and subsequently ameliorates the defects in TZ assembly initiation in cep290 mutants. Our results link CEP290 to DZIP1-CBY/Rab8 module and uncover a previously uncharacterized important function of CEP290 in the coordination of early ciliary membrane formation and TZ assembly.